The effect of the rhythm in the dramatic discourse of Colacho hermanos (1934) by César Vallejo - Ventura Vásquez, Williams Nicks (2022)
Studies about the poetry, tales and novels of César Vallejo evidence the poetic proceed and the exhaustive quest to elaborate an innovative artistic composition. That same literary encouragement is also perceived in the theatrical field, because the theoretical approaches and theatrical proposals show the interest in rethinking the dramaturgy of his time as he planted it in Colacho brothers (1934). This play, although the political, social and economic problem of peruvian society is highlighted, develop an incessant effort to achieve an theatrical discourse linked to its aesthetic inclination. Therefore, since a semiological and rhythmic perspective, this research focuses on verifying the composition of the dramatic dialogue in the play by the famous vate.